Sizzling sixteen - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2010)
Someone wants to kill Vinnie, but who? The list is long, and it's up to Stephanie to whittle it down to one in this 16th Stephanie Plum novel.